2013
DOI: 10.1172/jci65188
|View full text |Cite
|
Sign up to set email alerts
|

Liver acid sphingomyelinase inhibits growth of metastatic colon cancer

Abstract: Acid sphingomyelinase (ASM) regulates the homeostasis of sphingolipids, including ceramides and sphingosine-1-phosphate (S1P). These sphingolipids regulate carcinogenesis and proliferation, survival, and apoptosis of cancer cells. However, the role of ASM in host defense against liver metastasis remains unclear. In this study, the involvement of ASM in liver metastasis of colon cancer was examined using Asm -/-and Asm +/+ mice that were inoculated with SL4 colon cancer cells to produce metastatic liver tumors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…The upregulated cytokines [29, 30] we detected in culture supernatants of macrophages are known to promote tumor progression. Therefore, we further hypothesize that HG-NVs might enhance or increase tumor progression.…”
Section: Resultsmentioning
confidence: 99%
“…The upregulated cytokines [29, 30] we detected in culture supernatants of macrophages are known to promote tumor progression. Therefore, we further hypothesize that HG-NVs might enhance or increase tumor progression.…”
Section: Resultsmentioning
confidence: 99%
“…Another somewhat contradictory report showed that treatment of implanted hepatocellular carcinoma cells with both sorafenib (a multi-serine/threonine kinase inhibitor) and recombinant ASMase increased cell death relative to sorafenib alone [18]. This is backed up by a study showing that liver ASMase activity can inhibit the growth of metastatic colon cancer [19]. It therefore appears that the activity of ASMase in promoting cancer death may be tied to both the cell type and the protein kinases that are present.…”
Section: Part 1 Sphingolipids and The Initiation Of Apoptosismentioning
confidence: 99%
“…Notably in mice, an inhibitor of the interaction between β‐catenin and cyclic adenosine monophosphate‐response element‐binding protein‐binding protein (CBP) reduces liver fibrosis mediated by bile‐duct ligation (BDL), CCl 4 , or hepatitis C virus and prevents HSC activation, which results in a reduction of collagen expression in vitro . Liver macrophages contribute to liver fibrosis; depletion of liver macrophages suppresses liver fibrosis following BDL and decreases myofibroblasts in a liver tumor . Moreover, inhibition of CBP/β‐catenin promotes liver fibrosis resolution by macrophages .…”
Section: Introductionmentioning
confidence: 99%